Takhrij and Syarah Hadith of Agrotechnology: The Potential of Date Cultivation In Indonesia - Asyaliah Zahroh; Wahyudin Darmalaksana; Rani Widiana (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet regarding the cultivation of dates. This research method is qualitative through the takhrij and sharah hadith approaches with agrotechnological analysis. The results and discussion of this research is that the cultivation of dates in Indonesia has a very broad potential in cultivating dates and cultivating dates in Indonesia is very suitable and has proven successful. The conclusion of this study is that the takhrij and syarah hadith informs that dates have great potential because they have many benefits in the economic sector and in the health sector.